2019
DOI: 10.13053/rcs-148-5-8
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Recognition for Education using Sentiment Analysis

Abstract: Most systems that recognize emotions that are used in learning systems are oriented towards the detection of basic emotions such as happy, sad or angry. However, an intelligent tutor system must be able to detect, in a student, secondary emotions that have to do with learning as boring or frustrated. In the case of sentiment analysis in text, most of the research focuses on recognizing polarities (positive and negative). In this paper we present a sentiment analyzer for the recognition of polarities and emotio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Intelligent tutoring system (ITS) provides computerized self-paced and personalized learning module. Several studies have shown that ITS can benefits from ERS [34], [35]. Facial expression and self-assessment manikin are applied in [34].…”
Section: Emotion Recognition System In Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Intelligent tutoring system (ITS) provides computerized self-paced and personalized learning module. Several studies have shown that ITS can benefits from ERS [34], [35]. Facial expression and self-assessment manikin are applied in [34].…”
Section: Emotion Recognition System In Educationmentioning
confidence: 99%
“…Facial expression and self-assessment manikin are applied in [34]. On the other hand, the learners' state of emotion is identified via text data mining in [35]. The textual comments of leaners on the lesson and activities conducted are analyzed and the emotions are classified.…”
Section: Emotion Recognition System In Educationmentioning
confidence: 99%
“…Secondly, sentiment scores tend to be calculated from grouped or set averages, which lead towards gross over-averaging effects and concomitant loss of information [ 2 , 5 ]. In this study, we address the above drawbacks by expanding calculations of sentiment polarity [ 11 , 24 , 25 ], orientation of the expressed sentiment (positive, negative or neutral) and sentiment polarity shifts–which can help capture significant emotional changes [ 26 ]. Our proposed feature set, Emotional Variance Analysis (EVA), captures and profiles changes in sentiment polarity and intensity to accurately classify emotional instability [ 10 , 15 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Barron-Estrada et al. ( 2019 ) as the circumstances necessitated, these adjustments were implemented fast. Almost immediately, numerous educational institutions have begun to provide instructions and lectures through distance learning technologies (Zhao and Watterston 2021 ; Neuwirth et al.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, educators and educational institutions worldwide made a concerted effort to adapt and innovate. Barron-Estrada et al (2019) as the circumstances necessitated, these adjustments were implemented fast. Almost immediately, numerous educational institutions have begun to provide instructions and lectures through distance learning technologies (Zhao and Watterston 2021;Neuwirth et al 2021) changes in teaching delivery elicited a swift and enthusiastic response from educators.…”
Section: Introductionmentioning
confidence: 99%